Correlation of CuO2 superconducting planes deformation with superconducting critical temperature - González, J. C. (2015)
In the copper oxide superconductor materials the internal charge transference between the superconducting planes of CuO2 and the charge reservoir blocks, it is a key factor that control the superconducting critical temperature. The superconducting planes of CuO2 are not planes in a strict sense, the position of the Cu(2) atom and the O(2), O(3) oxygen atoms are not lying in a same plane, the change of its positions are closely related to atomic replacements in the superconducting planes of CuO2 or in the charge reservoir blocks. Therefore, we correlates the substitutions effects in the canonical unit cell of YBa2Cu3O7 with regard to length and angle bond variation of copper and oxygen atoms with the superconducting critical temperature obtained by Rietveld refinement of x-ray diffraction patterns in polycrystalline powder samples, such as: SmBa2Cu3O7, [Y0.90,Pr0.10]Ba2Cu3O7, [Ca,La]Ba2Cu3O7 and YBa2Cu3O7.